Perancangan Strategi Pemasaran Produk Sepeda Motor Merk Honda dengan Menggunakan Metode SWOT dan QFD - Marcy Lolita Pattiapon (ARIKA, 2011)
Research about customer satisfaction at the dealer MPM Honda motor cycle dealer has been conducted to investigate the appropriateness between customer needs and satisfactions. The problem become more crisis when the sale level at dealer MPM decrease. The purpose of knowing the priority attribut is dealer MPM become know their customer satisfactions so they can formulate the right marketing strategic for them. Collecting and analyzing data from quistioner give attribut value about motor cycle service quality that is wanted by the customer and this data also gives technical responds for dealer MPM. QFD analysis gives HOQ result that show customer priority attributes, these are the speed and accuracy of service process, monthly installment is attainable, low down payment, service after sales and giving special discount. The gaps of customer needs priority show that service quality of dealer MPM are not satisfaction the customer yet. It can be seen that a few attributes have negative value from the gap and from SWOT analysis we can see that dealer MPM position is in first room the space between strenght, opportunity, so we support strategic. Priority strategic that is being suggested are giving the price variation, spreading pamphlets, doing cooperation with liasing and bank, creating surprise packet, doing promotion at village and giving special discount.